El presupuesto por resultados y su influencia en la gestión de la municipalidad provincial de Virú 2016 - Guillen Urcia, Anaey Lizeth (2018)
The present research work has carried out in face of the problem of Local Governments administering the allocated resources in an adequate manner, showing in the Budget by Results of each institution. The general objective that encompasses the research is determine how the Budget for Results influences the Management of the Provincial Municipality of Viru in 2016. Whose study material of the research has a population of 84 participating agents of the Participatory Budget of the year 2016 whose random sample is 69 people, the correlational research method was used. The results of the investigation were favorable because the Provincial Municipality of Viru has obtained a satisfactory fulfillment of each one of its budgetary instruments of the year 2016 and thus reaffirms that the fulfillment of the Budgetary Evaluation has been worked according to the laws, norms, guidelines and indicators that the Ministry of Economy and Finance has indicated for the public sector. It is concluded that the Budget for Results through its various instruments and indicators has had a positive influence on the management of the Provincial Municipality of Viru since it showed an evaluation of the adequate execution.